POLITICAL AND PSYCHOLOGICAL IMAGE OF MODERN RUSSIA IN THE MASS CONSCIOUSNESS OF THE GENERATION - Valery I. Ketsba; Bata I. Ketsba (Вестник Московского государственного областного университета, 2020)
Aim. To identify the political image of Russia as it exists in the mass consciousness of its citizens within the age group of 56 and over.Methodology. This study is based on the results of sociological surveys conducted by the Department of Sociology and Psychology of Politics of Moscow State University. The surveys were conducted in Moscow, Tyva, the Republic of Dagestan, Saratov, Bryanskaya, Smolensk, Tomsk and Chelyabinsk regions. Both qualitative and quantitative methods were used to interpret the gathered data (focused semi-standardized interviews, drawing test and coding of the gathered data). Through those methods the author has identified the image of Russia as it exists in the mass consciousness of Russian citizens. Results. This study showed that the political and psychological image of Russia in the minds of respondents contains more attractive than negative characteristics. The positive components of the image of Russian statehood and people occupy the dominant position in the minds of Russian citizens and practically neutralize such negative associations as corruption, bad roads, etc. Moreover, the image of the country is not completely holistic and has slight differences at a rational and unconscious level of perception. At the rational level, the political power of Russia in the opinion of respondents is less negative than at the unconscious level. Research implications. The research results described in this article are of particular practical value for political psychologists and government officials, since any state strategy is ineffective if it does not take into account the mood of society and does not receive support from it.